Analysis Analysis of Judge's Ruling No. 58/Pid.B/2022/Pn.Kaltara Regarding the Criminal Act of Empliance in Office - Hidayat, Syarif; Handayati, Nur (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2024)
The criminal act of embezzlement in office, known as embezzlement with aggravation, is regulated in Article 374 of the Criminal Code. Article 374 of the Criminal Code states broadly the definition of the criminal act of embezzlement in office, however the criminal act of embezzlement in office itself consists of subjective elements in the form of intentional elements and unlawful elements as well as objective elements in Article 374 of the Criminal Code in the form of acts of possession, elements of objects. crime (an object), partly or wholly belonging to another person and where the object is in his control not because of the crime. The aim of the author in conducting a study in this research is to find out the Public Prosecutor's Indictment regarding the criminal act of embezzlement in office and to find out the Legal Considerations by the Panel of Judges in Imposing Sentences as in one of the criminal cases of embezzlement in office which is in the Decision. The problem approach in this research uses a normative juridical approach. The normative juridical approach is an approach through library research by reading, quoting and analyzing legal theories and statutory regulations related to the problems in the research. The research results include: (1). The judge's decision in case No. 58/Pid.B/2022/PN Kaltara has fulfilled the elements of the crime of embezzlement in office as regulated in Article 374 of the Criminal Code. The perpetrator, who was an employee of PT Manasseh Abadi Sentosa, was proven to have embezzled company funds for personal gain, which caused financial losses for the company. (2). The findings of this research emphasize the importance of strict internal supervision and periodic audits in preventing criminal acts of embezzlement in office. In addition, there is a need to increase employees' understanding of ethics and law at work through regular training.